Freedom without permission : bodies and space in the Arab revolutions - Hasso, Frances Susan; Salime, Zakia (Online access with subscription: Duke University Press., 2016)
In a series of case studies focusing on the Arab spring revolutions, the contributors to Freedom without Permission reveal the centrality of the intersections between body, gender, and space to the revolutions, showing how a diverse group of women and girls publicly disputed gender and sexual norms.